Trans-Sourcing Strategy For Service Project Deployment at PT. Indosat - Mansur, Labib; Gadre, Milind (The Indonesian Journal of Business Administration, 2012)
Nowadays, every cellular operator facing tough competition and already jump in on â€œprice warâ€ competitions. Every operator competes to offer very cheap pricing structure with a lot of feature and benefit to grab their customers. In other hand, the trend of network element equipment and serviceâ€™s pricing are decreasing from the supplier that lead to lower investment cost. But the decreasing of investment cost which gained by cellular operator still canâ€™t compensate the profit resulting from the decreasing of very cheap pricing of its products. These phenomena indicated clearly from their financial statement report especially on Revenue Growth and the ARPU (Average Revenue per User). In order to create new market and also to cater the existing customer growth, every year Indosat have to expand the network to broader its coverage and to enlarge its network capacity. One of the big contributions of the investment cost is the services cost. Every operator, include Indosat, continuously innovates to get an over of par value between the investment cost and the revenue. Therefore, one of the alternative solutions is coming from the optimization of the investment services cost. Â Keywords: decreasing revenue, high investment cost, optimization investment services cost.